2009
DOI: 10.1021/ci900299a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multilabel and Single-Label Classification Applied to the Prediction of the Isoform Specificity of Cytochrome P450 Substrates

Abstract: Each drug can potentially be metabolized by different CYP450 isoforms. In the development of new drugs, the prediction of the metabolic fate is important to prevent drug-drug interactions. In the present study, a collection of 580 CYP450 substrates is deeply analyzed by applying multi- and single-label classification strategies, after the computation and selection of suitable molecular descriptors. Cross-training with support vector machine, multilabel k-nearest-neighbor and counterpropagation neural network m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…In reality a significant proportion of xenobiotics are metabolized by more than one isoform. This was addressed in a recent study employing multi-label classifiers such as SVMs, multilabel k-NNs and ANNs [278] based on a set of 580 substrates of seven P450 isoforms (approx. 15% of these substrates are known to bind to up to five enzyme variants).…”
Section: Modeling Studiesmentioning
confidence: 99%
“…In reality a significant proportion of xenobiotics are metabolized by more than one isoform. This was addressed in a recent study employing multi-label classifiers such as SVMs, multilabel k-NNs and ANNs [278] based on a set of 580 substrates of seven P450 isoforms (approx. 15% of these substrates are known to bind to up to five enzyme variants).…”
Section: Modeling Studiesmentioning
confidence: 99%
“…In order to realize a better understanding of the function of chloroplast proteins, a proposed MLC algorithm was applied in prediction of protein subchloroplast locations in chloroplast organelle [27]. It was also shown that when the MLC approach is compared to a single label classification, it coherently reflects the actual metabolism information when applied over a collection of CYP450 substrates [30]. Multi-label Naïve Bayes classification models were constructed to improve target prediction for relevant target proteins over a wide set of chemical compounds [31].…”
Section: Introductionmentioning
confidence: 99%
“…21 There are two main types of multilabel methods: problem transformation and algorithm adaption methods. Problem transformation methods involve transformation of the multilabel data into single label data to then carry out conventional single label classification.…”
Section: Introductionmentioning
confidence: 99%